The Preservation of Tayub As An Effort To Sustain Traditional Performing Arts in The Community of Pati Regency - komariyah, isti; Jazuli Jazuli; Syahrul Syah Sinaga4; Udi Utomo5 (Universitas Negeri Semarang, 2025)
Tayub is a traditional Javanese art form featuring female dancers performing movements alongside male dancers, accompanied by Javanese gamelan music and traditional Javanese songs or gendhing. This study aims to analyze strategies for preserving Tayub as an effort to sustain traditional arts within the community of Pati Regency. A qualitative approach with a case study design was used in this research. Data collection techniques included observation, interviews, and documentation. The validity of the data was ensured through data triangulation. Data analysis techniques involved data reduction, data presentation, and conclusion drawing/verification.The findings revealed that the Tayub performance consists of three stages: the initial stage, the core stage, and the closing stage. Efforts to preserve Tayub in Pati align with Sedyawati's theory, encompassing protection, development, and utilization. Protective efforts are carried out through training and competitions. Utilization efforts involve performances, while developmental efforts focus on innovations in movements, accompaniment, and costume design.